RNA Sequencing Reveals LINC00167 as a Potential Diagnosis Biomarker for Primary Osteoarthritis: A Multi-Stage Study - Jiang, Liying; Zhou, Yiqin; Shen, Junjie; Chen, Yi; Ma, Ziyuan; Yu, Yuhui; Chu, Minjie; Qian, Qirong; Zhuang, Xun; Xia, Shengli (Frontiers in Genetics, 2021)
Objectives: In view of the roles of lncRNA in human diseases and the high incidence of OA, the study was investigated to explore pivotal pathways involved in disease and identify potential biomarkers for OA diagnosis. Methods: We first performed an exploration of RNA-sequencing in peripheral blood leukocytes from six subjects (3 OA and 3 healthy controls). The promising candidate lncRNAs were evaluated in the first stage validation using GEO dataset (GSE114007) of 38 subjects (20 OA and 18 healthy controls), followed by a second stage validation using quantitative PCR analysis within 101 subjects (67 OA and 34 controls). The third stage was performed to investigate the potential value of validated lncRNA in early diagnosis of OA in peripheral blood leukocytes from a total of 120 participants (60 cases and 60 controls). Results: Briefly, a total of 1,380 up-regulated and 719 down-regulated mRNAs and 5,743 up-regulated and 7,384 down-regulated lncRNAs were identified in our dataset. The up-regulated DEGs were mainly enriched in extracellular matrix, while the down-regulated DEGs were mainly enriched in pathways of IL-17 signaling pathway and wnt signaling pathway. 18 overlapped candidate lncRNAs survived after the first-stage validation. 3 hub lncRNAs were selected into the second validation stage and qualified in an external sample, and lncRNA LINC00167 was further confirmed with similar result (down-expressed in both stages). Receiver operating characteristics analysis showed that LINC00167 can distinguish OA cases from healthy controls with high area under the curve of 0.879 (95%CI: 0.819, 0.938; P<0.001), with sensitivity of 80.7% and specificity of 83.5%. Conclusions: The expression profile of OA was identified and critical pathways were elucidated by an integrated approach of RNA-seq from easily accessible blood. LINC00167 may serve as a potential early diagnosis marker for OA in clinical practice. The detailed mechanism of action of this lncRNA remains to be elucidated in the future.